To solve the equation 5/3x + 11/3 = -4/3, we can start by subtracting 11/3 from both sides to isolate the term with x:
5/3x + 11/3 - 11/3 = -4/3 - 11/3
This simplifies to:
5/3x = -15/3
Now, we can multiply both sides of the equation by the reciprocal of 5/3, which is 3/5, to solve for x:
(3/5)(5/3x) = (3/5)(-15/3)
The 3/5 on the left side of the equation cancels out with the 5/3 on the right side, leaving us with:
x = -9/5
The equation 5/3x+11/3=−4/3 is solved as follows. Fill in the correct numbers to complete the solution.(1 point)
3 answers
The equation 53x+113=−43 is solved as follows. Fill in the correct numbers to complete the solution.(1 point)
53x+113=−43
53x=
Subtract 113 from both sides.
x=
Multiply both sides by 35, the reciprocal of 53.
53x+113=−43
53x=
Subtract 113 from both sides.
x=
Multiply both sides by 35, the reciprocal of 53.
This is only for this question.
1. 5/3x= -5
2. x = -3
1. 5/3x= -5
2. x = -3